Information modelling and knowledge bases XXVIII - Jaakkola, Hannu (Frontiers in Artificial Intelligence and Applications, 2017)
The conference provides a platform to bring together researchers and practitioners working with information modelling and knowledge bases, and the 33 accepted papers cover topics including: conceptual modelling; knowledge and information modelling and discovery; linguistic modelling; cross-cultural communication and social computing; environmental modelling and engineering; and multimedia data modelling and systems.